Efficacy and safety of colistin for the treatment of infections caused by multidrug-resistant gram-negative bacilli - Kagami, Keisuke; Ishiguro, Nobuhisa; Yamada, Takehiro; Niinuma, Yusuke; Iwasaki, Sumio; Taki, Keisuke; Fukumoto, Tatsuya; Hayasaka, Kasumi; Oyamada, Reiko; Watanabe, Tsubasa; Nishida, Mutsumi; Sugita, Junichi; et al. (Journal of infection and chemotherapy : official journal of the Japan Society of Chemotherapy, 2021)
The efficacy and safety of colistin for the treatment of infections caused by multidrug-resistant gram-negative bacilli have been poorly investigated in Japanese patients. This study was performed to investigate the efficacy and safety of colistin in Japanese patients by analyzing a considerable number of cases. Furthermore, we evaluated the relationship between the plasma concentration and efficacy and safety of colistin in some cases. A retrospective cohort study was conducted at Hokkaido University Hospital, analyzing patients treated with colistin (colistimethate sodium) during the period from January 2007 to December 2019. Overall, 42 cases were enrolled. Favorable clinical response was observed in 25 cases (59.5%), with an all-cause 30-day mortality of 33.3% (14/42 cases). Microbiological eradication was achieved in 18 cases (42.9%). Nephrotoxicity was observed in 20 cases (47.6%) and was mild and reversible in all cases. Plasma trough concentrations of colistin determined in nine patients correlated with changes in serum creatinine concentration (⊿) and creatinine clearance (%). The cutoff value of colistin trough concentration for nephrotoxicity was 2.02 μg/mL. Our results showed approximately 60% clinical efficacy of colistin therapy against infections caused by multidrug-resistant gram-negative bacilli in the patients. Further studies with larger populations are needed to elucidate the efficacy and safety of colistin in Japanese patients.